NILAI RETENSI NITROGEN DAN ENERGI METABOLIS RANSUM MENGGUNAKAN DAUN MURBEI (Morus alba) SEGAR PADA BROILER - Dady, Zebedeus; Mandey, J. S.; Imbar, M. R.; Regar, M. N. (Universitas Sam Ratulangi, 2016)
NITROGEN RETENTION AND METABOLIZABLE ENERGY OF MULBERRY (Morus alba) FRESH LEAVES IN DIET OF BROILERS. The study was determine to evaluate the effect of Mulberry (Morus alba) fresh leaves in diet on nitrogen retention and metabolizable energy corrected for nitrogen of broilers. A total of 20 birds at age of 6 weeks old were used for 7 days of preliminary period and 3 days of data collection period using a completely randomized design with four treatments and five replications. The dietary treatment was including levels of 0, 2, 4, and 6% of fressh mulberry leaves in the diets. The variables were nitrogen retention (NR) and metabolizable energy corrected for nitrogen (AMEn). Results showed that there were significant differences (PË‚0.05) among treatments for NR and highly significant differences (PË‚0.01) among treatments for AMEn. Analysis of variance for NR showed that there was no significant difference between R0 (89.81%) and R1 (85.97%) of diets. Similarly, there was no significant difference between R1 (85.97), R2 (84.51%) and R3 (84.09%) of diets. The values ofÂ AMEn showed that R0 diet had significant difference with those of R1 (3517.80 Kcal/Kg), R2 (3451.73 Kcal/Kg) and R3 (3360.90 Kcal/Kg). However, between R1, R2, and R3 had no significant differences. The results suggested the experiments of mulberry fresh leaves in level up to 6% can be used as an alternatives feedstuff of broiler diet based on nitrogen retention and metabolizable energy corrected for nitrogen. KeyÂ words: broiler, murbei leaves, nitrogen retention and metabolic energy corrected nitrogen